KARAKTERISTIK PEMBAKARAN BRIKET LIMBAH JARAK DAN SEKAM PADA BERBAGAI KOMPOSISI - Irwan Paserangi (Universitas Fajar, 2016)
Results briquette making distance with wasp nests form in six samples, each sample weight was 1000 grams of raw materials with a concentration of 0% -50% composition range of waste and rice husk. The results showed briquette with composition 0 % husks have the time, temperature and the highest calorific value. Results of research on combustion of briquettes in real time using briquette stoves showed that the addition of the composition (%) effect on decreasing husk briquette combustion time and maximum temperature are obtained. Results of laboratory studies showed that the addition of the composition (%) husks effect on decreasing calorific value of briquettes. Husk serves as a trigger to burn a distance with a mixture of chaff on the composition of waste briquettes used in the amount of 10% range. The test results by analyzing the chemical composition estimates, test results through the analysis proksimasi thermal properties and physical properties, generally fall within the existing standard briquettes (briquettes commercial standard reference, import, Japan and USA). comparison with the test results indicate use of kerosene stoves and range of waste husks briquettes are more economical Rp. 500,00 if compared with the use of kerosene to boil 1 liter of water.